2020
DOI: 10.3389/fnhum.2020.00018
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Vocal Pitch Compensation in Individuals Who Stutter

Abstract: Stuttering is a disorder that impacts the smooth flow of speech production and is associated with a deficit in sensorimotor integration. In a previous experiment, individuals who stutter were able to vocally compensate for pitch shifts in their auditory feedback, but they exhibited more variability in the timing of their corrective responses. In the current study, we focused on the neural correlates of the task using functional MRI. Participants produced a vowel sound in the scanner while hearing their own voi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 93 publications
1
5
0
Order By: Relevance
“…Instability in forward and inverse models within the feedback control system could mean that while in some cases appropriate corrective commands can be generated, instability of modelling at other points results in a failure to initiate the compensation response sufficiently quickly. Such instability in the formation of internal models could be underwritten by the weakened communication between auditory and motor regions reported by Sares et al (2020). Similarly, this would fit with the account proposed by Hickok et al (2011), which suggests that noisy/variable forward predictions result from disruption to area Spt which coordinates the mapping between motor and sensory areas.…”
Section: Pitch Shift Studiessupporting
confidence: 52%
See 2 more Smart Citations
“…Instability in forward and inverse models within the feedback control system could mean that while in some cases appropriate corrective commands can be generated, instability of modelling at other points results in a failure to initiate the compensation response sufficiently quickly. Such instability in the formation of internal models could be underwritten by the weakened communication between auditory and motor regions reported by Sares et al (2020). Similarly, this would fit with the account proposed by Hickok et al (2011), which suggests that noisy/variable forward predictions result from disruption to area Spt which coordinates the mapping between motor and sensory areas.…”
Section: Pitch Shift Studiessupporting
confidence: 52%
“…Despite this lack of behavioural differences, Sares et al (2020) did nevertheless find differences in underlying neural activation between PWS and control participants who did not stutter. PWS were found to show deactivation of the middle temporal gyrus (MTG) and superior frontal gyrus (SFG) in the right hemisphere for shifted versus unshifted trials; conversely, PWNS showed increased activity in these areas for shifted versus unshifted trials.…”
Section: Pitch Shift Studiesmentioning
confidence: 76%
See 1 more Smart Citation
“…In comparison with primary auditory processing in the aSTG, researchers considered MTG to be related with higher level processing of auditory stimuli [ 91 , 92 , 93 ]. Previous research found greater activation in the bilateral MTG in both speech comprehension and production tasks [ 18 , 62 ], which suggested that the recruitment of the left MTG might reflect a higher level auditory processing of feedback, especially in terms of sensory integration [ 62 ]. In the current study, significant activation in the left MTG was detected in the PWNS, but no activation in this region was detected in the PWS.…”
Section: Discussionmentioning
confidence: 99%
“…Further, aPAS may also represent an intervention tool. Recent studies highlighted the potential therapeutic benefits of using PAS in neurological conditions such as stroke (Silverstein et al 2019) or incomplete spinal cord injury (Ling et al 2020); along those lines, aPAS may represent a viable intervention for audiomotor conditions, such as stuttering (Sares et al 2020). To achieve this, future studies should confirm the optimal ISI.…”
Section: Occlusion Of Ltp-like Plasticity After Trainingmentioning
confidence: 99%